REMARKABLE CORRELATION OF NON-GENETIC FACTORS WITH GROWTH TRAITS IN TWO BREEDS OF SHEEP - Aljubouri, T. R. S.; Hassan, A. F.; Al-Shuhaib, M. B. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted at the college of agriculture – Al-Qasim Green University to investigate the effect of breed and age of dams on several growth traits of two sheep breeds, including 123 Iraqi Awassi and 78 Iranian Karakul breeds. Variables growth traits were examined in the present study, namely body weight (BW), body length (BL), wither height (WH), rump height (RH), and chest circumference (CC), and abdominal circumference (AC). Results indicated the absence of a significant effect between both breeds in all investigated growth traits in birth. Meanwhile, a significant (P<0.05) superiority of Karakul over Awassi was detected in month-3 in three growth traits (BW, WH, and RH), and in month-6, in four growth traits (BW, WH, RH, and BL). The age of dams exhibited a significant (P<0.05) effect on the majority of lambs’ growth traits since lambs born from dams aged over 4 years gave more values than those born from dams aged less than 4 years. Sex of lambs had also contributed to growth traits measurements since higher values were collected from several growth males over females in month-3 (BW, BH, and RH), and month-6 (BW, BL, WH, and RH). Time of birth had also yielded significantly (P<0.05) better values for lambs born in January over those born in other months. However, lambs born in December gave better traits than other lambs. In conclusion, this study demonstrated the obvious superiority of Karakul over Awassi breed in the majority of growth traits measured.